Artificial intelligence, society 5.0 and smart city adaptation initiatives for businesses: An integrated approach - Gil, I. A. M.; Ferreira, F. A. F.; Ferreira, N. C. M. Q. F.; Smarandache, F.; Khanam, M.; Daim, T. (Technovation, 2026)
The mass migration of human populations to urban areas has resulted in unprecedented challenges for city services. To address and find solutions for these emerging issues, decision-makers must embrace the smart city and Society 5.0 paradigms, which comprehensively tackle various dimensions of the problem and ensure adaptability to evolving citizen needs. Central to the success of these paradigms is technology, particularly artificial intelligence (AI). AI’s transformative capabilities enable the expansion of services, automation of tasks, efficient operationalization and processing vast amounts of data to address urban challenges, aligning with several sustainable development goals (SDGs) such as sustainable cities and communities (SDG 11). Municipalities require strategic plans that empower them to adapt to the AI, Society 5.0 and smart city paradigms, involving multiple stakeholders, including businesses. This study presents a multi-criteria analysis system designed to support decision-making in this complex context, considering the subjective nature and inherent complexity of the decision problem. The system development involved input from key decision-makers with relevant expertise, utilizing methodologies such as cognitive mapping and the decision-making trial and evaluation laboratory technique applied in a neutrosophic environment to analyze cause-and-effect relationships between factors affecting adaptation initiatives. Based on a constructivist, process-oriented approach, the developed analysis system can assist decision-makers in navigating uncertainty during evaluations of technology integration. This holistic and comprehensive system promotes informed decision-making within the AI, Society 5.0 and smart city contexts, contributing to the achievement of relevant SDGs.